Equal protection of the law?: Gender and justice in the United States - Atwell, Mary Welek (Studies in crime & punishment, 2002)
Definitions, examples, and analytical tools -- Citizenship, constitutional rights, and equality : elusive goals -- Participating in the criminal justice system -- Women and girls as victims -- Victims and offenders : gender as the link -- Punishing women : the experience of female offenders -- Regulating reproduction -- Concluding thoughts